PEMBUATAN MESIN PEMERAS, JAHE UNTUK INDUSTRI KECIL KOPI , JAHE BUBUK - Darmono, Darmono (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2015)
The voucher program entitled "Manufacturing Ginger Squeezer Machine for Small Powder Ginger-Coffee Industries" aims to increase productivity of the UD. ROSE KURNIA especially in squeezing basic material of ginger as a substance for Powder Ginger-Coffee and Coconut Sugar Ginger being produced. It also wants to know the suitable size and productivity of such ginger squeezer machine., The steps of this manufacturing ginger squeezer machine are planning, machine manufacturing, and training for industry partner workers. The planning step includes: (1) designing machine plan draft, (2) calculating the needed materials, and (3) calculating the implementation cost. The machine-manufacturing step includes: (1) material cutting to fit the work draft, (2) welding, (3) assembling, (4) electric installation. (5) machine performance test, and (6) painting. The training for industry partner workers consists of: (1) theory and speech delivery, (2) demonstration of machine using, and (3) machine using practice by the industry partner workers.The result of the voucher program is realization of a squeezer ginger machine and skill achievement by the industry partner workers in the machine operation. The squeezer ginger machine was made of right-angled iron frame sizing 50x50x5 mm, combined with plywood of 3 mm and 12 mm thick. The machine size is 120 em length, 60 em width, and 190 em height, moved by a gasoline motor power HONDA of 4 HP and rotation speed of 1400 RP;-’1, The crushing system runs by 2 cylindrical tubes with 20 em diameter rotating in the opposite direction. The machine performance and productivity for squeezing ginger has speed of 4 to 5 times faster compared with manual squeezing system having been done up till now. Key words: ginger squeezer machine, and small powder ginger-coffee industry.